2021
DOI: 10.1017/s0025100321000116
|View full text |Cite
|
Sign up to set email alerts
|

Voicing of glottal consonants and non-modal vowels

Abstract: Variation in voicing is common among sounds of the world’s languages: sounds that are analyzed as voiceless can undergo voicing, and those analyzed as voiced can devoice. Among voiceless glottal sounds in particular, voicing is widespread: linguists often expect the voiceless glottal stop [ʔ] and fricative [h] to be fully voiced, especially between vowels. In this study, we use audio recordings from Illustrations of the International Phonetic Alphabet published in the Journal of the International Phonetic Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 92 publications
2
15
0
Order By: Relevance
“…In this view, laryngeal features are licensed by prosodic structure, and never analysed as segments, largely in line with the proposal made by [64]. In a similar vein, Garellek et al [36] suggested that while treating a glottal stop as a segment may be useful for phonological analysis, the actual phonetic realization of a glottal stop (or glottalization) can be better characterized as modulation of phonation gesture (with a range of phonetic implementation that may vary with prosodic structural factors), which poses challenges for treating it as segmental.…”
Section: The Prosody Account: a Glottal Gesture Is Prosodic In Naturesupporting
confidence: 77%
See 4 more Smart Citations
“…In this view, laryngeal features are licensed by prosodic structure, and never analysed as segments, largely in line with the proposal made by [64]. In a similar vein, Garellek et al [36] suggested that while treating a glottal stop as a segment may be useful for phonological analysis, the actual phonetic realization of a glottal stop (or glottalization) can be better characterized as modulation of phonation gesture (with a range of phonetic implementation that may vary with prosodic structural factors), which poses challenges for treating it as segmental.…”
Section: The Prosody Account: a Glottal Gesture Is Prosodic In Naturesupporting
confidence: 77%
“…However, these considerations are contingent on whether a glottal stop with a full closure is indeed a hyperarticulated phonetic form that enhances its underlying representation as just discussed above [24][25][26][27]. In fact, as was noted by Davidson [35], it is not often the case that a glottal stop is realized with a full closure across languages [see also 36,37]. For example [35], showed that a phonemic glottal stop in Hawaiian is most often realized as creaky voice especially in a word-medial intervocalic context with flanking vowels being 'glottalized.'…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations